416 Prospective Multicentre Study of Impact of COVID-19 on Colorectal Cancer Resections. (4th May 2021) - Kumar, L; Mahfooz Buksh, M; Merali, N; Hammer, C; Nagendram, S; Kenny, R; Chakravartty, S; Madan, R
Abstract: Introduction: COVID-19 pandemic has posed a major challenge to healthcare systems globally. In NHS, around 36, 000 cancer operations have been estimated to be cancelled during the peak time alone. This regional study evaluated the risk of COVID-19 in patients undergoing surgery for colorectal cancer during the peak time. Method: This prospective multicentre observational study conducted in four busy district hospitals included 52 patients with colorectal cancer who underwent surgery during the COVID lockdown period (23 rd March to 5 th May). PCR swab testing was used to detect COVID. Data was collected from patient notes, MDT files and pathology results. Results: 73% (38/52) underwent elective procedures, 90% with curative intent. Overall, mean (SD) age was 70 (12.2) years, 50% were female. 60% (32/52) had left sided cancers and a total of 48% (25/52) patients had stage 3 or above. 27% (14/52) had post-operative complications, with 4% (2/52) being Grade 3 Clavien-Dindo. Total mortality was 6% (3/52) of which 1 was elective patient. Only one patient developed COVID infection during the inpatient stay. Conclusions: Data suggests, local policies to prevent COVID spread have been effective. Local lockdown in case of second peak may be a reasonable option. Improvement in COVID testing could have major impact on outcomes.